Dignity at the End of Life: Lessons from the COVID-19 Pandemic for End-of-Life Care in Africa - BECQUÉ, Yvonne N. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2026)
The COVID-19 pandemic exposed profound fractures in the capacity of health systems worldwide to ensure dignified death, yet nowhere were these fractures more consequential than across the African continent, where pre-existing deficits in palliative care infrastructure intersected catastrophically with viral containment imperatives. This paper examines the lessons that the pandemic yields for reimagining end-of-life care in Africa, arguing that the crisis has made visible what was long known but insufficiently addressed: the systematic neglect of dying as an essential component of health and humanitarian response. Drawing on diverse examples from South Africa, Uganda, Kenya, Zimbabwe, Zambia, and other African nations, the analysis interrogates how pandemic restrictions on family presence, communal mourning, and traditional death rituals collided with deeply held cultural understandings of personhood and communal obligation, producing forms of suffering that exceeded the physical trajectory of disease. The paper traces how community-based palliative care models, task-shifting initiatives permitting nurse-prescribing of morphine, and culturally grounded bereavement practices offer instructive counter-narratives to the technocratic, hospital-centric approaches that dominated pandemic response. The work is structured across five interconnected themes: the right to dignity as a foundational principle, the disruption of familial and communal caregiving, the cultural violence enacted through mortuary protocols, the critical shortage of opioids and trained personnel, and the neglect of bereavement as a public health concern. The analysis demonstrates that dignity at the end of life in African contexts cannot be secured through the simple transplantation of Western palliative care frameworks but requires sustained engagement with local moral economies, community structures, and postcolonial realities. The paper concludes by advancing recommendations for integrating palliative care into universal health coverage, reforming restrictive opioid prescription laws, embedding culturally competent death practices within emergency preparedness, and recognizing family caregivers as essential partners in care delivery.